Getting to the Point? Reframing Narratives on Knife Crime. (April 2020) - Harding, Simon
Amid rising public concern of knife-enabled crime, this article seeks to review and reframe the contemporary debates on knife crime which remain tied to concepts of fear, protection and fashion. Concepts of social field theory and street capital theory have much to offer in reframing a more contemporary narrative. Through such analysis, knife crime can be redefined as a logical response to the unpredictable asymmetrics of the social field, offering mechanisms for agency and control while providing both a pressure release and opportunity to demonstrate authenticity in 'The Game'.